Effects of coagent incorporation on properties of ultrafine fully vulcanized powdered natural rubber prepared as toughening filler in polybenzoxazine. (24th February 2021) - Wongkumchai, Rattanaporn; Amornkitbamrung, Lunjakorn; Mora, Phattarin; Jubsilp, Chanchira; Rimdusit, Sarawut
Abstract: Ultrafine fully vulcanized powdered natural rubber (UFPNR) is a renewable material that is promising for industrial application as a toughening filler in polymer matrix. In this work, effects of coagent on properties of UFPNR produced by radiation vulcanization and spray‐drying was systematically investigated, in which trimethylol propane trimethaacrylate (TMPTMA) was used as coagent. The crosslinking density of UFPNR could be enhanced by increasing radiation dose from 50 to 350 kGy and it was further enhanced by using TMPTMA as coagent during the production process. UFPNR with the smallest particle size of 3.9 ± 1.8 μm and highest thermal stability ( T d5  = 347°C) could be obtained by using TMPTMA with the highest content of 9 phr. The results suggested that polymer chains of natural rubber were more packed into smaller particle as they were more crosslinked by the coagent. Finally, an application of UFPNR as a toughening filler in polybenzoxazine was demonstrated. The highest impact strength improvement of 20% was achieved by incorporation of 3 phr UFPNR in polybenzoxazine. Abstract : Ultrafine fully vulcanized powdered natural rubber (UFPNR) was produced by radiation vulcanization and spray‐drying. During the production, trimethylol propane trimethaacrylate (TMPTMA) was used as a coagent to enhance crosslinking density and reduce particle size of UFPNR from 8.5 μm to 3.9 μm. UFPNR was used as a toughening filler in polybenzoxazine with the highest impact strength improvement of 20%.